Kontribusi Pasar Saham Syariah Terhadap Pertumbuhan Ekonomi Indonesia - Shofiatul Jannah, Binti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
Contribution of the Islamic Stock Market to Indonesia's Economic Growth. This study aims to investigate the contribution of the development of the Islamic stock market to Indonesia's economic growth. Gross domestic product (GDP) is the market value of all goods and services produced by a country in a certain period. GDP is one method for calculating national income. The Islamic stock index used is the Jakarta Islamic Index (JII) which has long standing. Therefore, the research sample consists of the JII (Jakarta Islamic Indexs) and GDP (Gross Domestic Product). The research period is approximately 16 years of observation ranging from 2000 to 2016. Data was obtained from publications on the IDX (Indonesia Stock Exchange) website, OJK (Otoritas Jasa Keuangan) and BPS (Badan Pusat Statistik). Some tests such as the root unit test, cointegration test and Error Correction Model are used to test data. The statistical test tool used was Eviews 9. The Error Correction Model results show that the Islamic stockl market does not affect long-term economic growth.